Games, Ideas and Activities for Early Years Literacy - Coulson, Gill and Cousins, Lynn (New Dehli Pearson, 2014)
Description Games, Ideas and Activities for Early Years Literacy provides a wealth of activities to supplement and support the teaching of literacy in a fun and appealing way in any early years setting. The learning objectives identified within each activity will help any early years practitioner integrate the activities into their planning and are based on the principles of the EYFS curriculum.?
Include Illustrations
Keywords: Picture books for children